THE ARTIFICIAL INTELLIGENCE AND ITS GLOBAL ECONOMIC GROWTH IMPACT - Salih M. Sahi (Scholar Express Journals, 2022)
Artificial intelligence (AI) is the skill of any mechanical gadget to mimic human intelligence. AIis created for generating technologies potentially increasing productivity and economic welfare. The main objective of the article is to show the key role that AIare playing in the national economies to global transformations. This paper basically spins around ideas, challenges, and uses of AIand economic growth. However, this paper providessignificant implications for policymakers, especially during an economic transformation. Theevidence showed AI largely influences economy. This study used international organizations’ statistics related to the AI-economic growth to collect AI data. The latter has special data sources such as International Federation of Robotics(IFR),McKinsey Global Institute,World Bank, OECD, and PricewaterhouseCoopers (PwC) Global. The economic efficiency of AI for individual industries or enterprises is not questioned. This allows us to conclude that individual positive results did not become universal due to objective circumstances and require further research in this direction
Keywords: Artificial intelligence; AI market; robotics; economic growth